Doubly-excited pulse waves on thin liquid films flowing down an inclined plane: An experimental and numerical study - Adebayo,I; Xie,Z; Che,Z; Matar,O (Physical Review E, 2017)
The interaction patterns between doubly excited pulse waves on thin liquid films flowing down an inclined plane are studied both experimentally and numerically. The effect of varying the film flow rate, interpulse interval, and substrate inclination angle on the pulse interaction patterns is examined. Our results show that different interaction patterns exist for these binary pulses, which include solitary wave behavior, partial or complete pulse coalescence, and pulse noncoalescence. A regime map of these patterns is plotted for each inclination angle examined, parametrized by the film Reynolds number and interpulse interval. Finally, the individual effect of the system parameters mentioned above on the coalescence distance of binary pulses in the “complete pulse coalescence” mode is studied; the results are compared to numerical simulations of the two-dimensional Navier-Stokes equations yielding good agreement.